Corporate Governance and Board Effectiveness Amid Technological Disruption in Lagos State Civil Service Commission - Okonmah, Anthony Iweanya; Alade, Adebola (Universitas Medan Area, 2025)
This study examines corporate governance and board effectiveness within the Lagos State Civil Service Commission, focusing on how digital technologies and information systems are strategically employed to enhance governance, decision-making, and service delivery between 2018 and 2025. A descriptive qualitative research design was adopted. Data were collected through semi-structured interviews with key administrative staff and the content analysis of institutional policy documents and strategic reports. Findings reveal that the Commission has adopted several digital platforms to streamline operations and improve transparency; however, their utilisation varies considerably across administrative levels due to factors such as the digital divide, organisational culture, and infrastructural resilience. Significant gaps were identified in data governance, cyber-resiliency, and citizen engagement systems, which limit the Commission’s progress toward digital maturity and transformation. The study underscores the need for proactive and adaptive governance in responding to technological disruption. It recommends implementing tiered capacity-building programmes, organisational change management, data governance frameworks, strategic citizen engagement, and integrating digital governance objectives into the civil service reform agenda. If adopted systematically, these measures could strengthen institutional resilience, enhance stakeholder trust, and align governance practices with modern public sector ideals.